Confronting the democratic discourse of librarianship: A Marxist analysis: Review of the book Confronting the democratic discourse of librarianship: A Marxist analysis by Popowich, S - McNichol, Michael (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2020)
Review of the book Confronting the democratic discourse of librarianship: A Marxist analysis by Popowich, S